Citizens' use of digital media to connect with health care: Socio-ethical and regulatory implications. (July 2019) - Petersen, Alan; Tanner, Claire; Munsie, Megan
Digital technologies promise to transform practices of health, medicine and health care and 'power' economies. In expectation of their presumed future benefits, governments in recent years have invested heavily in new technology initiatives and have sought to engender 'digital literacy' among citizens. This article introduces papers and expands on themes arising from a special issue that explores the socio-ethical and regulatory implications of citizens' use of digital media to connect with health care. We set the scene by examining the promissory discourse that attaches to digital technologies as applied to health care, and its role in shaping actions, and then consider the longer term prospects and implications of digitalisation for conceptions of citizenship and established categories and distinctions. As we argue, given the history of new technologies, the longer term implications of digitalisation are likely to differ significantly from those envisaged. Digital technologies promise radical positive disruption. Yet many uncertainties accompany their development and future applications and likely implications. Making reference to papers in the special issue and the wider literature, the article considers the prospects of digitalisation in medicine and health care in light of the colonisation of the Internet by powerful technology companies, the shift in capitalist economies from processes of production to technologies of prediction, evidence of inequalities in access to the Internet and related devices, and the growing number of data breaches involving personal health information. We draw attention to the failure of governments to engage citizens in substantive deliberations about digitalisation and its future potential implications and the ultimate democratic deficit that this represents. We ask, what does it mean to 'regulate' digital media in a context in which data are widely viewed as the 'new oil'? While we have no straightforward answers, we suggest that recent legislative efforts (e.g. General Data Protection Regulation in Europe) and growing calls for 'algorithmic accountability' have the potential to temper the more harmful aspects of digitalisation.